Knowledge, risk perception and quantification of hepatitis b surface antigen antibodies in clinical laboratory w (Revista Venezolana de Salud Pública, 2021)
Hepatitis B virus (HBV) is the etiologic agent of a universally distributed liver disease, causing chronic infection, cirrhosis, and liver cancer. A descriptive, non-experimental, cross-sectional study was carried out between May-June 2019. This research inquired about the knowledge, forms of contagion, professional risk behaviors and quantified the levels of HBsAb antibodies in the samples of clinical analysts working in the area. of the Clinical Laboratory of the provinces of Orellana and Napo, belonging to the Zonal Coordination 2-Health (MSPE-Z2) in Ecuador. The population was made up of 77 professionals with the hepatitis B vaccination certificate. Blood samples were taken and processed in the INSPI laboratory in the city of Tena. The survey was used as an instrument to collect information about the knowledge that the workers had about this pathology and a form to record results of the levels of antibodies against HBsAg and response classification. It was found that 64% (49/77) of the participants were female and 36% (28/77) were male. The predominant age group in the study sample was
Keywords: Antibodies; Hepatitis B